The Artist as culture producer living and sustaining a creative life - Louden, Sharon (Bristol, UK Intellect Books, 2017)
When Living and Sustaining a Creative Life was published in 2013, it became an immediate sensation. Edited by Sharon Louden, the book brought together forty essays by working artists, each sharing their own story of how to sustain a creative practice that contributes to the ongoing dialogue in contemporary art. The book struck a nerve – how do artists really make it in the world today? Louden took the book on a sixty-two-stop book tour, selling thousands of copies, and building a movement along the way. Now, Louden returns with a sequel: forty more essays from artists who have successfully expanded their practice beyond the studio and become change agents in their communities. There is a misconception that artists are invisible and hidden, but the essays here demonstrate the truth – artists make a measurable and innovative economic impact in the non-profit sector, in education and in corporate environments. The Artist as Culture Producer illustrates how today's contemporary artists add to creative economies through out-of-the-box thinking while also generously contributing to the well-being of others. By turns humorous, heartbreaking and instructive, the testimonies of these forty diverse working artists will inspire and encourage every reader – from the art student to the established artist. With a foreword by Hyperallergic co-founder and editor-in-chief Hrag Vartanian, The Artist as Culture Producer is set to make an indelible mark on the art world – redefining how we see and support contemporary artists.
Keywords: Artists -- United States -- Biography; Artists -- Biography; Artists and community -- United States; Art, Modern; Art and society -- United States